(untitled) (Gragoatá, 2018)
Mateship is an important element of the so-called “Australian Tradition” in literature. It consists of a particular bond between men who travel the rural areas known as “the bush” or “the outback”. This article examines some of Henry Lawson’s mateship stories, with a focus on the different connotations that the term can assume for the author, especially regarding the theme of egalitarianism. It considers how the Bulletin Magazine, which “discovered” Lawson and published many of his stories, had a role in fostering a special model of Australian democracy and a peculiar style for Australian literature. It also reflects on how the dissemination of Lawson’s stories through periodicals in the last decades of the 19th century helped create a feeling of what Benedict Anderson calls “nation-ness”. ———————————————————————————— MATESHIP E IGUALITARISMO NOS CONTOS DE HENRY LAWSON Mateship é um elemento importante da chamada “Tradição Australiana” na literatura. Refere-se a um vínculo especial entre homens que percorrem as áreas rurais conhecidas na Austrália como “the bush” ou “the outback”. Este artigo examina alguns dos contos de Henry Lawson que trazem esse elemento, com ênfase especial nas diferentes conotações que o termo pode assumir para o autor, especialmente com relação à temática do igualitarismo. O artigo considera como o periódico Bulletin, o qual “descobriu” Lawson e publicou vários de seus contos, foi relevante para a promoção de um modelo particular de democracia na Austrália e um estilo característico para a literatura local. O artigo também reflete sobre como a disseminação dos contos de Lawson por meio de periódicos na última década do século XIX contribuiu para a criação do que Benedict Anderson chama de “nation-ness”. — Artigo em inglês. — DOI: http://dx.doi.org/10.22409/gragoata.2018n45a1057.